The Tradition of Moantar Nasi a Procession in Baralek Events At Weddings - Astuti, Astuti; Endrizal; Edi Satria (Kirana Publisher (KNPub), 2023)
This study discusses the tradition of moantar nasi, a procession in the baralek event at a wedding ” aims to find out how the moantar nasi procession takes place in the baralek event and also wants to know the symbolic meaning and the food and equipment brought at the time of rice moantar procession. Moantar nasi is a procession in the baralek event and also the highlight of a wadding held at the marapulai house. The research was conducted using observational data collection techniques (observation) and in-depth interviews. (in-depth interviews). Using a qualitative method with an approach that produces descriptive data.The results of this study explain the first, the form of the procession of the moantar nasi tradition which starts from the preparation stage in the form of timbang tando, preparing food, preparing tools and materials, then at the implementation stage there are monoguar activities, handing over katidiang, saying goodbye. The second explains the symbolic meaning found in food and equipment.The meaning of an odd number of foods and utensils contained in the moantar nasi tradition is basically a symbol of love and liking, as found in the moantar nasi tradition, starting from an odd number of rice, an odd number of flowers, an odd number of shawls, and an odd number of chickens. also an odd number, all of which have a meaning, namely that a husband and wife must always have a feeling of love and liking for their partner until death separates them. Moantar nasi has a goal, namely to establish intimacy.